2018
DOI: 10.1115/1.4040353
|View full text |Cite
|
Sign up to set email alerts
|

A Transmission Quality Index for a Class of Four-Limb Parallel Schönflies Motion Generators

Abstract: This paper presents a uniform method of evaluating both transmission quality and singularity applicable for a class of parallel Schönflies-motion generators (SMGs) with four RRΠRR limbs. It turns out that the determinant of the forward Jacobian matrices for this class of parallel robots can be expressed as the scalar product of two vectors, the first vector being the cross product of the four unit vectors along the parallelograms, and the second one being related to the rotation of the mobile platform (MP). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In accordance with the singularity analysis of this four-limb parallel SMG [33,34], the constraint singularity usually occurs when at least two of the parallelograms are parallel or the rotational sub-platform lies in the plane determined by the two parallelograms in the first and third limbs [9]:…”
Section: Constraint Singularitymentioning
confidence: 80%
See 3 more Smart Citations
“…In accordance with the singularity analysis of this four-limb parallel SMG [33,34], the constraint singularity usually occurs when at least two of the parallelograms are parallel or the rotational sub-platform lies in the plane determined by the two parallelograms in the first and third limbs [9]:…”
Section: Constraint Singularitymentioning
confidence: 80%
“…From the perspective of workspace quality, the proposed robot can have a relatively large fullrotation workspace free of singularity versus the robot footprint, rather than some existing four-limb SMGs as revealed in our previous work [34]. Moreover, in comparison with the four-limb SMG end-effectors with different shape and size corresponding to different orientations, e.g., belt-pulley mechanism [4], the rack-pinion mechanism [3], gears and screw mechanism [5], an advantage is that the articulated transmitting mechanism can be sealed in the gearbox, which eases the cleaning procedure when the robot is deployed in the sector of food industry.…”
Section: Mechanical Design and Comparison With Smg Counterpartsmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, some scholars found that the determinant of the Jacobian matrices for a class of parallel robots can be expressed as the scalar product of two vectors, and then the pressure angles, derived from the determinants of the Jacobians, can be used for the evaluation of the transmission quality, the detection of robot singularities, or the kinematic constraints of optimal design. [17][18][19] Since the reciprocal product of a unit wrench and a unit twist is irrelevant to the coordinate frame, the virtual coefficient was proposed. 20 Based on such a concept, a variety of kinematic performance evaluation indices, which are dimensionless and invariant with respect to the coordinate frame, are constructed.…”
Section: Introductionmentioning
confidence: 99%